2456. Immunogenicity and Safety of a MenACWY-CRM Booster Dose 4–6 Years After Primary Quadrivalent Meningococcal Conjugate Vaccination in Healthy US Adolescents and Adults. (26th November 2018) - Tipton, Mary; Daly, Wendy; Senders, Shelly; Block, Stanley L; Keshavan, Pavitra; Mzolo, Thembile; Pellegrini, Michele
Abstract: Background: Neisseria meningitidis serogroups A, B, C, W, and Y are a leading cause of bacterial meningitis and sepsis worldwide. Infants <1 year, adolescents and young adults are at the highest risk. The US Advisory Committee on Immunization Practices (ACIP) recommends routine MenACWY conjugate vaccination for adolescents at 11–12 years of age, with a booster dose 5 years later. We examined responses to a booster dose of MenACWY-CRM given 4–6 years after primary vaccination with a licensed quadrivalent meningococcal conjugate vaccine (NCT02986854). Methods: 602 adolescents and adults aged 15–55 years who had received either MenACWY-CRM ( N = 301) or MenACWY-D ( N = 301) 4–6 years earlier, and a control group of vaccine-naïve participants ( N = 102) were enrolled at 37 centers across the US and 701 overall received a single dose of MenACWY-CRM at Day 1, across study groups. Immunogenicity was evaluated pre-vaccination, either 4 or 6 days post-vaccination (sampling subgroups) and 29 days post-vaccination by serum bactericidal activity assay using human complement (hSBA). After vaccination, all participants were to be monitored for 7 days for reactogenicity, 29 days for unsolicited adverse events (AEs), and 6 months for occurrence of medically attended events, AEs leading to withdrawal and serious AEs. Results: Sufficiency of the immune response to a booster dose of MenACWY-CRM was demonstrated as the lower limit of the 1-sided 97.5% confidence interval for percentages of participants with hSBA seroresponse for each serogroup at 29 days post-vaccination was >75%, both in participants primed with MenACWY-CRM and MenACWY-D. Independent of quadrivalent meningococcal vaccine priming, >93% of participants achieved a seroresponse at day 29 post-booster. By day 6 post-booster, >47% of primed participants achieved hSBA titers ≥1:8 for MenA, >87% for MenC, >93% for MenW and >85% for MenY, and by day 29 almost all primed participants had seroprotective titers across all serogroups. Overall, the vaccine was well tolerated across participants in all 3 groups and no safety concerns were raised. Conclusion: MenACWY-CRM induced robust boosting in adolescents and adults primed with a quadrivalent meningococcal conjugate vaccine 4–6 years earlier, with an acceptable clinical safety profile. Funding: GSK Biologicals SA. Disclosures: S. L. Block, GSK: Research Contractor, Research support. P. Keshavan, GSK Vaccines: Employee, Salary. T. Mzolo, GSK Vaccines: Employee, Salary. M. Pellegrini, GSK Vaccines S.r.l.: Employee and Shareholder, Salary.